The effect of marketing spending on sales in the premium car segment: New evidence from Germany - Jesus Crespo-Cuaresma; Matthias Stoeckl (University of Salzburg, Department of Social Sciences and Economics, 2012)
This paper assesses empirically the relationship between marketing expenditures and sales in the premium car segment in Germany. We employ a new data-set which contains model-specific data on sales (i.e. registrations), restyling activities and marketing expenditures at a monthly basis for the years 1998 to 2007. The richness of our data in the time dimension allows for a systematic modeling of product life cycle effects which have been partly ignored in the existing empirical literature. We find a robust positive marketing-sales relationship, even after common characteristics of the product life cycle have been taken into account. Furthermore, our results indicate that the launching of a new model, face lifts and customized packages appear to exert a positive and sizeable effect on sales in the German premium car segment.
Keywords: D43; M31; M37; 330; Marketing expenditure; panel data models; automobile industry; premium car segment; automotive restyling